2011
DOI: 10.1002/cncr.26424
|View full text |Cite
|
Sign up to set email alerts
|

Annual screening strategies in BRCA1 and BRCA2 gene mutation carriers

Abstract: Background While breast cancer screening with mammography and MRI is recommended for BRCA mutation carriers, there is no current consensus on the optimal screening regimen. Methods We used a computer simulation model to compare six annual screening strategies [film mammography (FM), digital mammography (DM), FM and magnetic resonance imaging (MRI) or DM and MRI contemporaneously, and alternating FM/MRI or DM/MRI at six-month intervals] beginning at ages 25, 30, 35, and 40, and two strategies of annual MRI wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(56 citation statements)
references
References 27 publications
0
55
0
1
Order By: Relevance
“…In many studies, mammography and MR imaging were performed within 90 days of one another (10, 15,33). A modeling study reported that the most efficacious screening strategy for carriers of BRCA mutation was to start screening with MR imaging annually at age 25 and to add annual mammography at age 30, staggering the two examinations at six month intervals (34). In our study, the decision to perform both studies synchronously or at 6-month intervals was determined by the patient and her clinician.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, mammography and MR imaging were performed within 90 days of one another (10, 15,33). A modeling study reported that the most efficacious screening strategy for carriers of BRCA mutation was to start screening with MR imaging annually at age 25 and to add annual mammography at age 30, staggering the two examinations at six month intervals (34). In our study, the decision to perform both studies synchronously or at 6-month intervals was determined by the patient and her clinician.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the following criteria were applied: modeling studies were eligible when evaluating the radiation induced risk in BRCA1/2 mutation carriers; clinical case-control or cohort studies were included if estimating the BC risk in BRCA mutation carriers who underwent mammography or chest X-ray (CXR) or any kind of radiological breast exposures. Computer simulation models comparing radiological screening strategies such as Lowry and colleagues' article (Lowry et al, 2012) are not in the scope of this review dedicated to radiation-induced BC effects.…”
Section: Introductionmentioning
confidence: 99%
“…The FH01 trial has shown evidence of a reduction in advanced stage disease with yearly mammographic surveillance in women aged 40-49 years with a medium familial risk of breast cancer [20]. In BRCA mutated women, it seems that annual MRI at age 25 and delayed alternating digital mammography at age 30 is probably the most effective screening strategy, despite false positives and radio-induced cancers [21].…”
Section: Family History Of Breast Cancermentioning
confidence: 99%